Determinants of Success: Lessons to be Learned From Rail Transit System Development in Miami-Dade and Dallas Counties - Patrik BELL; Gina SCUTELNICU; Susan YOUNG (Transylvanian Review of Administrative Sciences, 2007)
The Miami Metro Transit Authority Master Plan was originated 25 years ago, and its goals remain largely unmet. In approximately the same time period the Dallas Area Rapid Transit Authority has completed its phase one plan. Using a comparative approach, this study seeks to elucidate transportation model outcomes which are suitable to region specific needs. Our investigative intent is twofold. First, our analysis will yield policies that facilitate greater functionality in terms of access and time-efficient methods of transportation. Second, the analysis will reveal policies and factors influencing transportation outcomes in geographically dispersed locales such as Miami Dade County and Dallas County. This analysis will seek to explain the failure or the success of the public transit development with attention paid to political and technical factors. Experiences in these two Sunbelt metropolises will shed light on policies that might enhance public transit development elsewhere.